The Development and Effect of E-Libraries: Revolutionising Knowledge Access - Gupta, Devang (Journal of Advanced Research in Library and Information Science, 2023)
Numerous facets of contemporary life have been profoundly altered by the digital revolution, libraries are no exception. E-Libraries, usually referred to as electronic libraries, have become a potent and cuttingedge response to the persistent problems of information access and dissemination. This review article examines the development and effects of electronic libraries on learning, research, the dissemination of knowledge in general. It talks about the benefits and drawbacks of this technological development, how user experiences have changed, how it might affect libraries in the future. This article highlights significant achievements, technological developments, efforts that have impacted the E-Library environment through an in-depth analysis of the historical development of E-Libraries. The paper emphasises how E-Libraries have promoted remote learning, research cooperation, lifelong education by outlining the myriad advantages of E-Libraries, including unrestricted accessibility, quick availability, support for varied learning styles. The essay does acknowledge some of the difficulties faced by e-libraries, such as copyright issues, problems with digital preservation, the digital divide. Despite these difficulties, e-libraries have had a profound influence on research and education, giving researchers greater access to material and building a global community of scholars. The paper explores the role that user experience and interface design play in raising user happiness and engagement with e-libraries. In order to predict how the landscape of e-libraries will change, the essay makes predictions about prospective future breakthroughs including augmented reality integration and AI-driven information curation. In conclusion, e-libraries have transformed how people engage with information. Despite ongoing difficulties, they offer enormous promise to democratise knowledge and promote education. In order to promote a more inclusive, connected, educated global community as the world develops, library science must seize the opportunities provided by this digital revolution.